The cytokine system’s status in bacterial dysbiosis and bacterial vaginosis - Hruzevskyi, Oleksandr (ScienceRise: Medical Science, 2020)
Interrelations of conditionally-pathogenic microflora and vaginal mucosa’s APC are realized by forming of proinflammatory and regulatory cytokines which can provoke bacterial dysbiosis progression and bacterial vaginosis development. The aim of the study: to determine cytokine system’s status in the blood and vaginal fluid in bacterial dysbiosis and bacterial vaginosis. Material and methods. There were used data from 298 women, divided into groups according to the index of conditionally pathogenic microflora and normobiota index: normocenosis (n=53); grade I bacterial dysbiosis (n=128); and grade II bacterial dysbiosis (n=117). In the last group 83 patients with normobiota index >1 lg GE/sample, with bacterial vaginosis isolated. The posterolateral vaginal paries epithelium scrapings examined with PCR: facultative and obligate anaerobes, myco- and ureplasms and yeast fungi were quantified. Contents of IL in VF and in the serum were studied with enzyme-linked immunosorbent assay. For statistical analysis Statistica 10 soft (StatSoft, Inc., USA) was applied. Results. Blood interleukins’ contents increased with progressing of bacterial dysbiosis, and was maximal in bacterial vaginosis: 3,0-6,0 times (p<0,001) more than in normocenosis. Levels of these interleukins were: interleukin-1β > interleukin-6>interleukin-8>tumour necrosis factor-α > interleukin-2; in vaginal fluid: interleukin-6> tumour necrosis factor-α > interleukin-1β>interleukin-8> interleukin2. Content of γ-interferon in blood and vaginal fluid was higher in bacterial dysbiosis, and was less in manifested bacterial dysbiosis and bacterial vaginosis (comparing to normocenosis). Interleukin-4 and interleukin-10 levels were less in the blood and vaginal fluid along to the progressing of bacterial dysbiosis. Transforming growth factor-1β level in the blood was more in bacterial vaginosis only, whereas in vaginal fluid –in bacterial dysbiosis and bacterial vaginosis. Among blood cytokines interleukin-1β levels correlated with index of conditionally-pathogenic microflora: its content more 24,6 pg/ml indicated bacterial dysbiosis-II, from 9,6 to 24,5 pg/ml –bacterial dysbiosis-I, and contents less than 9,6 pg/ml – normocenosis. Transforming growth factor-1β and interleukin-10 contents in vaginal fluid were suppressive. Conclusion. Obtained data confirmed determining role of cytokine system in bacterial dysbiosis progression and bacterial vaginosis development. Content of proinflammatory cytokines in the bloodstream increased with progressing of dysbiosis and reached maximum I bacterial vaginosis. Content of anti-inflammatory cytokines with progressing of dysbiosis decreased both in the bloodstream and vaginal fluid